Customer Identification in the Healthcare Industry. (November 2017) - Zhang, Long; Zhang, Yucheng; Jiang, Hong; Yang, Miles M.; Huang, Yu-Ying; Li, Shyh-Jane
This study investigates the key antecedents and mechanisms that influence customer identification in healthcare contexts, based on two studies from different stakeholders: healthcare workers and patients (customers) of healthcare organisations. The first study (N = 788) explored a positive relationship between a hospital's service tangibility and service reliability. The second (N = 657) affirmed and expanded this finding, and revealed that the service reliability of a hospital was positively related to customer identification with the hospital. This service reliability further mediated the positive relationship between service tangibility and customer identification. Our results highlight the role of service tangibility and reliability in enhancing customer identification in healthcare contexts. Implications for theory and practice are discussed.